"I Don't Take This Man to Be My Lawfully Wedded Husband": Considering the Criminal Offense of "Forced Marriage" and Its Potential Impact on the Lives of Girls and Young Women with Migrant Backgrounds in Germany. Issue 4 (1st September 2015) - Braun, Kerstin
Abstract : In Germany, the practice of forcing a person to marry against his or her own free will was not explicitly penalized and did not attract much political attention until the beginning of the new millennium. Since the mid-2000s, however, the German legislature has enacted a number of laws concerning forced marriage, possibly due to increased public and media interest in honor-related gender violence in immigrant communities. In 2011, the German Criminal Code (StGB) was amended to include "Forced Marriage, " thus making forcing someone to marry an offense in its own right. In light of similar recent developments criminalizing forced marriages in other European jurisdictions—such as England and Wales—this article aims to critically assess the German legislation and its potential impact on victims and offenders. First, this article considers the German criminal legislation in detail. Second, it contemplates the underlying question of whether the introduction of criminal law as a repressive measure effectively addresses the issue of forced marriage. Third, this article contemplates non-legislative measures that could contribute to affording more holistic protection. Finally, it concludes that improving the situation for victims of forced marriage in practice requires more than adopting criminal law on the matter.